Using Natural Language Processing Technology to Analyze Teachers’ Written Feedback on Chinese Students’ English Essays - Liu, Ming; Xu, Weiwei; Ran, Qiuxia; Li, Yawen (International Journal of Learning, Teaching and Educational Research, 2015)
Writing an essay is a very important skill for students to master, but a difficult task for them to overcome. It is particularly true for English as Second Language (ESL) students in China. It would be very useful if students can receive timely and effective feedback about their writing. In order to build an automatic feedback system, we need to understand the relationship between textual features and human teacher feedback, and how well those features were used for predicting feedback rating. In this study, we analyzed 105 Chinese English majors’ essays with teachers’ feedback and used Coh-Metrix, a computational linguistic tool, to extract features from their writing. The study results showed some feedback was moderately correlated to some textual features (e.g. text easability cohesion and lexical diversity were related to coherence feedback) and those feedback are more predictable, such as spelling, grammar, supporting ideas and coherence. This finding has important implications for building automated writing feedback tool.